2018
DOI: 10.1002/etc.4217
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term effects and recovery of streams from acid mine drainage and evaluation of toxic metal threshold ranges for macroinvertebrate community reassembly

Abstract: Monitoring of benthic invertebrates in streams receiving acidic metal-contaminated water over an 18-yr period revealed both degraded conditions and recovery along a network of downstream locations. Compared with reference streams, and over the course of clean-up remediation efforts below an abandoned open-pit sulfur mine in the central Sierra Nevada of California, improving water quality was accompanied by recovery of benthic communities at some sites. Years of high flow resulted in degraded biological status … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 42 publications
0
16
0
Order By: Relevance
“…In contrast, downstream communities remain dominated by metal‐tolerant species and show little evidence of recovery 15 years after restoration. This lack of recovery is surprising given that other investigators have reported rapid improvements in benthic communities following less dramatic reductions in metal concentrations (Herbst et al, ; Hornberger, Luoma, Johnson, & Holyoak, ). In addition, the proximity of a diverse and highly productive upstream source of colonists, a critical requirement for recovery from mining pollution in streams (Kitto et al, ; Swan & Brown, ), should have expedited recovery of this system.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…In contrast, downstream communities remain dominated by metal‐tolerant species and show little evidence of recovery 15 years after restoration. This lack of recovery is surprising given that other investigators have reported rapid improvements in benthic communities following less dramatic reductions in metal concentrations (Herbst et al, ; Hornberger, Luoma, Johnson, & Holyoak, ). In addition, the proximity of a diverse and highly productive upstream source of colonists, a critical requirement for recovery from mining pollution in streams (Kitto et al, ; Swan & Brown, ), should have expedited recovery of this system.…”
Section: Discussionmentioning
confidence: 90%
“…These differences in metal tolerance between communities persisted throughout the study, despite significant improvements in water quality over the past 15 years. Although several macroinvertebrate taxa from the upstream site were more sensitive to metals, the greatest difference between sites was observed for grazing mayflies, organisms known to be especially sensitive to mining discharges (Clements et al, ; Herbst, Medhurst, & Black, ; Mebane, Eakins, Fraser, & Adams, ).…”
Section: Discussionmentioning
confidence: 98%
“…Additionally, R. robusta develop to a much larger overall body size compared to Baetidae, potentially increasing its relative tolerance to metals . Metal exposure in the field is spatiotemporally variable, ,, and because aquatic insects exhibit complex life histories, our ability to characterize full-life cycle sensitivity with mesocosms is limited by the exposure duration and the phenology of the community. Moreover, our mesocosms are closed systems that do not allow for natural colonization.…”
Section: Discussionmentioning
confidence: 99%
“…To date, when evaluating the changes in stream environments near abandoned mining areas, only the water quality variables or the coarse level of benthic macroinvertebrate data (i.e., family level) have been used (but also see [ 34 , 35 ]), and descriptive or multivariate analyses have been applied to interpret the results. Network analysis [ 36 ], which has now been increasingly used to understand the interactions and stability of complex ecological communities, can provide undetectable insights compared with traditional analytical methods that analyze the species separately [ 37 , 38 ].…”
Section: Introductionmentioning
confidence: 99%